Implementing Software Containers in DevOps Practices for Quantum Computing - Kinanen, Otso (2024)
Quantum computing is an alternative computing paradigm gaining popularity in research, investment, and publicity. Quantum computers could provide exponential speed-ups for certain problems that are very hard to solve with current classical algorithms. As the development of quantum computing hardware has been accelerating, the need for specialized quantum software engineering is on the rise. This thesis researches the use of containerized application and demonstrate use cases with quantum hardware execution and with the use of Kubernetes cluster as an application executing quantum code.